A cultural perspective of higher education governance reform in Poland: divergent interpretations by rectors across distinct categories of universities. Issue 6 (2nd November 2022) - Donina, Davide; Pokorska, Anna; Antonowicz, Dominik; Jaworska, Marta
ABSTRACT: In 2018, a new governance law ( Ustawa 2.0 ) modernised the institutional governance of Polish public higher education institutions. This article investigates the governance changes from the cultural perspective of higher education governance through a survey administered to all Polish rectors. Responses were analysed by splitting higher education institutions into three categories (traditional academic [comprehensive], specialised, and applied sciences) to explore whether distinct institutional environments/subfields influence the perception of the new governance model. This article provides several research contributions: it is the first to adopt a cultural perspective to analyse higher education governance reforms in a Central and Eastern European country; it addresses specialised universities and universities of applied sciences, which are usually overlooked in higher education governance studies; and it extends the knowledge of the recent Polish higher education reform by highlighting divergent interpretations of the same governance framework across distinct institutional subfields within the same higher education system.